Protein Structure and Function Analysis Method of Aminoacyl-tRNA Synthetase Cofactor and Biotinylation Effect: Journal Review - Nugraha, Restu; Wang, Chien Chia; Widodo, Widodo (The Journal of Experimental Life Science, 2019)
Protein has been known as an important macromolecule which has a vital role among the living organism. One of the most interesting protein is Arc1p, which is a yeast-specific tRNA-binding protein. Arc1p is a unique protein that has the ability to form a ternary complex with glutamyl-tRNA synthetase (GluRSc) and methionyl-tRNA synthetase (MetRS) in the cytoplasm. This complex can significantly enhance the aminoacylation efficiency of these two aaRSs to their respective cognate tRNAs. Recently, it was found that Arc1p can be biotinylated via post-translational modification at Lys86 (K86) in the N-domain. Here, we try to figure it out what kind of method that will help to create some clear information both in structure and function of this protein, when mutations occur inside of the K86 site within SSKD motifs of Arc1p. Several methods to better understanding obviously about protein characteristics comprises protein structural analysis; such as gel mobility shift assay, CD Spectroscopy, and limited proteolysis; protein functional analysis, and in silico modeling.Keywords: Arc1p, biotinylation, function, in silico, structure.